A review and perspective for research on moisture damage in asphalt pavement induced by dynamic pore water pressure. (20th April 2019) - Wang, Wentao; Wang, Linbing; Xiong, Haocheng; Luo, Rong
Highlights: Moisture damage induced by dynamic pore water pressure exhibits a totally different failure mechanism. Newly proposed dynamic pore water pressure conditioning methods and their applications are reviewed. Relevant investigations on multiscale numerical simulation and field tests are analyzed. Challenges on current research and future works are discussed. Abstract: Under repeated vehicle loadings, surface runoff and retained water inside asphalt pavement structure will cause dynamic pore water pressure with positive and negative alternations. Such dynamic pore water pressure squeezes and pumps water flow along the inner wall of void channels to strip asphalt film and finally develop into moisture damage. Different from the traditional freeze-thaw and static water immersion mechanisms, dynamic hydraulic scouring induced by vehicle tires demonstrates a more general moisture damage of asphalt pavement in warm seasons or warm regions. This paper reviews extensive research works in the last decade about moisture damage of asphalt pavement induced by dynamic pore water pressure. A field survey of distresses characterization for an asphalt pavement is firstly introduced and analyzed. On the basis of analyzing macro-scale and micro-scale mechanisms of hydraulic scouring, traditional experimental methods for moisture damage evaluation are then discussed. Newly proposed three types of dynamic pore water pressure conditioning systems with their applications, which include pneumatic, piston and other types, are categorized and analyzed. Multiscale experimental investigations considering dynamic pore water pressure are discussed in detail. Numerical simulation on the water-mechanic response, moisture damage characteristics of asphalt pavement and the real-time monitoring of dynamic pore water pressure in field tests are also summarized. Finally, a series of measures to mitigate moisture damage from the perspective of dynamic hydraulic scouring is proposed.